Geography and Economic Development - Gallup, John Luke; Sachs, Jeffrey D.; Mellinger, Andrew D. (International regional science review, 1999)
Location and climate have large effects on income levels and income growth through their effects on transport costs, disease burdens, and agricultural productivity, among other channels. Geography also seems to affect economic policy choices. Many geographic regions that have not been conducive to modern economic growth have high population densities and are experiencing rapid increases in population. At particular disadvantage are regions located far from coasts and ocean-navigable rivers, for which the transport costs of international trade are high, and tropical regions, which bear a heavy burden of disease. Moreover, a large portion of population growth over the next thirty years is expected to occur in these geographically disadvantaged regions.